Colocasia esculanta L. (Talas): Kajian Farmakognosi, Fitokimia dan Aktivitas Farmakologi: Colocasia esculanta L. (Taro Plant): Study of Pharmacognosis, Phytochemical, and Pharmacological Activity - Vera Ladeska; Rino Andriano Am; Endang Hanani (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Taro plant (Colocasia esculenta L.) belongs to the Araceae family is one of the most widely grown plants in Indonesia, and is widely used as a food ingredient. In some countries this plant has long been used for traditional medicine. Until now, there has not been found a review of taro plants that includes biology, chemical content and properties. This study aims to review the taro plant (C. esculenta L.) in terms of pharmacognosy, phytochemical and pharmacological properties. The research is compiled based on journals that have been collected by both national and international journals. The results of the study stated that in Indonesia, various types of taro are grown. In the stems, leaves and tubers there are various chemical compounds, depending on the planting area. Taro has activity as an antioxidant (medium category), antimicrobial, antibacterial.